Promotion Strategies, Price, and Service Quality on Customer’s Booking Intention During the COVID-19 Pandemic (Case of Giszella Hotel, West Sumatra, Indonesia) - Jessica Afrila Neza; Mahir Pradana (Universitas Muslim Indonesia, 2021)
In this study, the authors researched one of the hotels located in the South Coast area, West Sumatra, namely Hotel Giszella. Hotel Giszella is one of the hotels frequented by local people and outside the region. However, due to the coronavirus pandemic, Hotel Giszella experienced several problems. The purpose of this study was to determine and analyze how promotional strategies, prices, service quality and consumer purchase interest at Giszella Hotel during the COVID-19 pandemic, as well as to assess the influence of promotional strategy, prices and service quality simultaneously and partially on consumer buying interest. Hotel Giszella at the time of the COVID-19 pandemic. This research uses quantitative methods with descriptive and causal research types. Sampling was done by using a non-probability sampling method with purposive sampling type. Data collection using a questionnaire with as many as 250 respondents and interviews. The data analysis technique used descriptive analysis and multiple linear regression analysis. Based on the results of the descriptive study of the promotional strategy variables, price, service quality and consumer purchase interest in Giszella Hotel during the COVID-19 pandemic, overall are in a suitable category. The results of the multiple linear regression analysis technique, promotion strategy, price and service quality simultaneously have a significant effect on consumer purchase interest in Giszella Hotel during the COVID-19 pandemic.